Occult Adenoma in Patent Vitellointestinal Duct Presenting as an Umbilical Fistula: Cause for Concern?. (3rd July 2016) - Bhankar, Himani; Goyal, Surbhi; Zaheer, Sufian; Sugandhi, Nidhi; Mandal, Ashish Kumar
ABSTRACT: Introduction : Prevalence of vitellointestinal duct anomalies varies from 2-4%. Though a completely patent vitellointestinal duct is a common symptomatic embryological defect with a prevalence of 0.0063–0.067%, other vitellointestinal abnormalities are rarely reported. Ours is the first case to describe histopathological features of an umbilical fistula harboring an occult tubular adenoma. Case Report : We report a case of one-month old child, presenting with umbilical fistula for which excision and ileal anastomosis was performed. Routine histopathologic examination revealed an occult tubular adenoma in tip of the fistula. Conclusion : Adenoma arising in an umbilical fistula at such an early stage of infancy has never been reported before. Detection of occult adenoma warrants screening GI endoscopy, genetic testing for syndromic gastrointestinal adenomatosis and carcinomas and lifelong surveillance. Our case highlights the importance of routine histopathologic examination in detection of occult premalignant lesions as it significantly affects the patient management and prognosis.